Perceptions of Injustice in Wives' Dual Roles and Divorce Petitions: A Communication Study in Modern Families - Dwi Budiyani, Ni Komang; Kartika, Tina; Besar, Ibrahim (IJESS International Journal of Education and Social Science, 2025)
Women who take on dual roles as both homemakers and breadwinners often face unequal burdens within the structure of modern families. While modernization has opened up space for women's participation in the public sector, traditional expectations regarding domestic responsibilities remain deeply rooted. This study aims to understand the perception of injustice in the dual roles of wives and its impact on decisions to file for divorce initiated by women. Using a qualitative approach, data were collected through in-depth interviews with women who experience dual roles and face divorce, supported by a literature review. The findings reveal that perceived injustice arises when husbands do not share domestic responsibilities, even when their wives also work outside the home. This imbalance creates tension in the household, especially when coupled with poor communication, lack of empathy, and third-party influences such as extended family. However, the study also highlights that a commitment to sharing responsibilities, honest communication, and flexibility in role-taking can serve as key factors in maintaining family cohesion. The research emphasizes that in modern families, role distribution should be based on equality and mutual understanding, rather than traditional gender constructs. Therefore, it is crucial for couples to build healthy communication and shared commitment to ensure that dual roles do not become a source of conflict leading to divorce.